2012
DOI: 10.1371/journal.pone.0033576
|View full text |Cite
|
Sign up to set email alerts
|

Morpholino-Mediated Increase in Soluble Flt-1 Expression Results in Decreased Ocular and Tumor Neovascularization

Abstract: BackgroundAngiogenesis is a key process in several ocular disorders and cancers. Soluble Flt-1 is an alternatively spliced form of the Flt-1 gene that retains the ligand-binding domain, but lacks the membrane-spanning and intracellular kinase domains of the full-length membrane bound Flt-1 (mbFlt-1) protein. Thus, sFlt-1 is an endogenous inhibitor of VEGF-A mediated angiogenesis. Synthetic mopholino oligomers directed against splice site targets can modulate splice variant expression. We hypothesize that morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…The soluble forms of the VEGF receptors bind to the ligand and block their angiogenic action (Kaczmarek et al, 2005). Cancer therapy studies have shown that an increase in the expression of sVEGFR1 (Owen et al, 2012) or sVEGFR2 (Wang et al, 2006;Szentirmai et al, 2008) reduce tumour cell proliferation and increase apoptosis (Szentirmai et al, 2008), which is associated with a reduction in blood flow to the tumour tissues. In the present study, mRNA expression of VEGFR2 on days 4 and 6 (CL formation) of the cycle was at least eightfold higher than that Figure 2 Changes in the ratio of mRNA expression for angiogenic (VEGF120a, VEGFR1 and VEGFR2) and antiangiogenic (VEGF120b, sVEGFR1 and sVEGFR2) VEGF system components in the corpus luteum during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble forms of the VEGF receptors bind to the ligand and block their angiogenic action (Kaczmarek et al, 2005). Cancer therapy studies have shown that an increase in the expression of sVEGFR1 (Owen et al, 2012) or sVEGFR2 (Wang et al, 2006;Szentirmai et al, 2008) reduce tumour cell proliferation and increase apoptosis (Szentirmai et al, 2008), which is associated with a reduction in blood flow to the tumour tissues. In the present study, mRNA expression of VEGFR2 on days 4 and 6 (CL formation) of the cycle was at least eightfold higher than that Figure 2 Changes in the ratio of mRNA expression for angiogenic (VEGF120a, VEGFR1 and VEGFR2) and antiangiogenic (VEGF120b, sVEGFR1 and sVEGFR2) VEGF system components in the corpus luteum during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases redirection of splicing to an aberrant isoform that is not normally generated from a gene transcript can be an effective means to eliminate a detrimental RNA isoform that is implicated in disease (Table 1, detrimental gene expression). Some of the more advanced studies, showing promise in animal models, include ASOs targeting TNFRSF1B 112 for the treatment of inflammatory disease, and FLT1 92 as a cancer therapy.…”
Section: Targeting Splicing In Disease: the Fixesmentioning
confidence: 99%
“…To date there are only twenty-eight studies using Vivo-morpholinos [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44] and all have reported at least 50% knockdown of the target gene with no adverse side effects. Fourteen of these studies used a mouse model [17], [18], [19], [20], [21], [24], [31], [32], [34], [35], [40], [41], [42], [43] with the remaining studies using rats [36], [37], newts [29], chicken embryos [27], fish [15], [16], [22], [23], [25], [26] tadpoles [30], [38], or frogs [28].…”
Section: Introductionmentioning
confidence: 99%